2017
DOI: 10.1142/s1793993317500089
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Demographics on Productivity and Inflation in Japan

Abstract: Is Japan’s aging and, more recently, declining population hampering its growth and reflation efforts? Exploiting the demographic and economic variation in the prefectural data between 1990 and 2007, we find that aging of the working age population has had a significant negative impact on the total factor productivity (TFP). Moreover, prefectures that aged at a faster pace experienced lower overall inflation, while prefectures with higher population growth experienced higher inflation. The results give strong s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 10 publications
1
26
0
1
Order By: Relevance
“…More recently, by constructing a DSGE model with demographic factors and financial frictions, Okazaki and Sudo (2018) also found that demographic changes (working-age population to be more precise) have had a negative and increasing impact on the natural rate of interest in Japan since early 2000s, and the impact is of similar magnitude as what we find in this paper. Moreover, our findings are also in line with empirical literature (e.g., Aiyar et al, 2016 andLiu andWestelius, 2017) which found that demographic changes have had significant effects on potential growth through reducing labor inputs and the growth rate of total factor productivity (TFP) in many advanced economies, including Japan.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…More recently, by constructing a DSGE model with demographic factors and financial frictions, Okazaki and Sudo (2018) also found that demographic changes (working-age population to be more precise) have had a negative and increasing impact on the natural rate of interest in Japan since early 2000s, and the impact is of similar magnitude as what we find in this paper. Moreover, our findings are also in line with empirical literature (e.g., Aiyar et al, 2016 andLiu andWestelius, 2017) which found that demographic changes have had significant effects on potential growth through reducing labor inputs and the growth rate of total factor productivity (TFP) in many advanced economies, including Japan.…”
Section: Introductionsupporting
confidence: 91%
“…Similarly, in a cross-country panel study for European countries, Aiyar et al (2016) found that workforce aging is associated with a reduction in TFP growth in Europe. Moreover, using a similar methodology but prefecture-level data on Japan, Liu and Westelius (2017) found that aging of the working-age population has had a significant negative impact on TFP in Japan. Feyrer (2007) found an inverted U-shaped relationship between the age distribution and TFP using a cross-country panel on OECD and low-income countries.…”
Section: Econometric Frameworkmentioning
confidence: 99%
“…As compared to medium-age workers (more generally, the working-age population), the elderly participate less actively in the labor force, their productivities are lower (Skirbekk, 2003;Aiyar, et al, 2016;Liu and Westelius, 2016), and they save less (Park and Shin, 2012;Horioka and Niimi, 2017). Thus, if a number of people in the working-age population are replaced by an equivalent number among the old-age population, other things being equal, then population aging in a country will hamper its economic growth, thus imposing a significant demographic burden.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the present research is to continue deepening the path opened by these authors and to contribute with ideas and data to a little researched field in the population ageing studies [21]. As far as the authors know, this is the first time that the possible relationship between ageing and productivity is analysed in Europe between 1983 and 2014, a period of special interest due to the pronounced ageing process experienced by European society [22] and the second wave of productivity increase identified in the USA and European countries between 1995 and 2004 [23].…”
Section: Introductionmentioning
confidence: 99%